Field test program and results to verify HPFF cable rating - Williams, J.A.; Bascom, E.C.; Aabo, T.; Horgan, B.M. (IEEE transactions on power delivery, 1992)
A summary of steps taken by one utility to obtain substantial increases in power transfer capability for an existing 115 kV pipe-type high pressure fluid filled (HPFF) cable circuit is presented. Test and analyses that were done to verify that the cable could achieve the new ampacity are described.< >